2018
DOI: 10.1088/1748-9326/aaeaeb
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of forest age in annual net forest carbon balance

Abstract: Forests dominate carbon (C) exchanges between the terrestrial biosphere and the atmosphere on land. In the long term, the net carbon flux between forests and the atmosphere has been significantly impacted by changes in forest cover area and structure due to ecological disturbances and management activities. Current empirical approaches for estimating net ecosystem productivity (NEP) rarely consider forest age as a predictor, which represents variation in physiological processes that can respond differently to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 79 publications
3
63
0
Order By: Relevance
“…A test of Odum's theory, using data from 39 temperate forest stands, found little evidence for a decline in net productivity for mid‐succession forests, 100–200 years old, and a slight decline for older forests (Curtis & Gough, ; Gough et al, ). Another study analyzed data from 126 forest sites and fit eddy covariance measurements of annual net ecosystem productivity (NEP) to the function that is dependent on stand age (Besnard et al, ). They found that an empirical model describes that the relation between NEP (g C m −2 year −1 ) and age (years) shows an asymptotic behavior:NEP=-324.7+587.7(1-exp(-0.2age)).…”
Section: What Have We Learned About Carbon Fluxes?mentioning
confidence: 99%
“…A test of Odum's theory, using data from 39 temperate forest stands, found little evidence for a decline in net productivity for mid‐succession forests, 100–200 years old, and a slight decline for older forests (Curtis & Gough, ; Gough et al, ). Another study analyzed data from 126 forest sites and fit eddy covariance measurements of annual net ecosystem productivity (NEP) to the function that is dependent on stand age (Besnard et al, ). They found that an empirical model describes that the relation between NEP (g C m −2 year −1 ) and age (years) shows an asymptotic behavior:NEP=-324.7+587.7(1-exp(-0.2age)).…”
Section: What Have We Learned About Carbon Fluxes?mentioning
confidence: 99%
“…Either ignoring such outliers or judging that a measurement bias by soil chambers affects all sites the same way (e.g. systematic overestimation of soil respiration in lowturbulence conditions when using static chambers, Braendholt et al, 2017), we may argue that the apparent decrease in both chamber / EC ratios R soil / GPP and R soil / R eco with N dep (Fig. 11a, c) has some reality, even if their absolute values are biased.…”
Section: Does Nitrogen Deposition Impact Soil Respiration?mentioning
confidence: 99%
“…Fifth, heterotrophic respiration of exuded photosynthate and dead plant material by microbes (Kuzyakov, 2010) and disturbance by fire, mortality, insects and pathogens, landslides or floods (Amiro et al, 2010) return an additional increment of carbon to the atmosphere on ecosystem time and space scales. And sixth, the ability of an ecosystem to sequester carbon will vary with its age (Besnard et al, 2018;Coursolle et al, 2012;Odum, 1969).…”
mentioning
confidence: 99%